PERFORMANCE OF MALE BALI DUCK (Anas sp.) WITH THE ADMINISTRATION OF PINEAPPLE PEEL EXTRACT (Ananas comosus (L). Merr) THROUGH DRINKING WATER - T.F., Indo,; Siti, N W.; Witariadi, N. M. (Jurnal Peternakan Tropika; Vol 12 No 5 (2024): Vol. 12 No. 5 Tahun 2024; September - October, 2024)
This study aims to determine the effect of administering pineapple peel extract through drinking water on the performance of male bali duck. This research was conducted at the Farm of Faculty of Animal Husbandry, Udayana University, located at Jalan Raya Sesetan, Gang Markisa No. 6, Denpasar, Bali, over a period of 8 weeks. The design used was a completely randomized design (CRD) consisting of four treatments and four replications. Each replication contained three male bali ducks with a homogeneous body weight 48.54 ± 2.58 g, so the total number of male bali ducks used was 48 male bali ducks. The four treatments were given pineapple peel extract through drinking water: (P0) without pineapple peel extract, (P1) 6% pineapple peel extract, (P2) 8% pineapple peel extract and (P3) 10% pineapple peel extract. The variables observed were initial body weight, feed consumption, drinking water consumption, final body weight, body weight gain and feed convertion ratio (FCR). The results showed that administration of pineapple peel extract at levels 6%, 8% and 10% via drinking water had no significant effect on the variables of intitial body weight, feed consumption, drinking water consumption, final body weight, body weight gain and feed convertion ratio (FCR). The results of this study can be conclude that administering pineapple peel extract through drinking water at levels 6%, 8% and 10% does not effect on the performance of male bali ducks.